Intergenerational Changing Patterns among the Siddi Tribe in Karnataka: A Sociological Study - Ananta Keshav Siddi; Dr. Ravi S. Dalawai (Revista Electronica de Veterinaria, 2024)
The Siddis are descendants of African slaves, sailors, and merchants who were brought to India by Portuguese and Arab traders, mainly between the 15th and 19th centuries. In Karnataka, the Siddis are mostly concentrated in the Uttara Kannada district, especially in the Yellapur, Haliyal, Ankola, and Mundgod taluks. Over time, notable shifts in population dynamics, such as changes in fertility rates, migration patterns, and age structure, have reshaped the social fabric of the tribe. These changes have influenced social mobility, economic conditions, education, and labor participation. The present study explores how these factors are interconnected in determining the socio-economic status of the Siddi tribe. A descriptive research design, both qualitative and quantitative methods have been used. The research examines the demographic and social transformations of the Siddi tribe over recent decades. Some Siddis have moved from rural to urban areas seeking economic opportunities, which has affected community cohesion and cultural integrity. Social mobility has progressed slowly, influenced by education, government initiatives, and economic shifts. While increased access to education has opened new career paths, challenges in attaining higher education still exist.